Cover Feature: Hybrid Sulfur−Selenium Co‐polymers as Cathodic Materials for Lithium Batteries (ChemElectroChem 2/2018). Issue 2 (13th December 2017) - Gomez, Iñaki; Mantione, Daniele; Leonet, Olatz; Blazquez, J. Alberto; Mecerreyes, David
Abstract : The Cover Feature represents the merging of sulfur and selenium into new hybrid co‐polymers, which show excellent performance as cathodes in lithium batteries. More information can be found in theArticle by I. Gomez et al. onpage 260 in Issue 2, 2018 .